Simulated Secondary Mechanical Recycling of Pla Water Bottles: Insights into Structural Integrity, Barrier Performance, and Biodegradability - Velasquez, E (Elsevier B.V., 2026)
The presence of compostable packaging in the market has increased driven by growing environmental concerns regarding plastic pollution. However, certain biopolymers, such as poly (lactic acid) (PLA) represent high-value materials whose compostability may lead to a loss of valuable resources. In this study, the impact of the mechanical recycling of commercial PLA-based plastic water bottles and subsequent reprocessing on their structural and technological properties was investigated for the first time with the objective of evaluating its recyclability and potential further use. The mechanical recycling simulation included photochemical, thermal, hydrothermal, and washing processes, followed by extrusion reprocessing. Structural analyses revealed the occurrence of chemical modifications, such as chain scission and increased melt fluidity, that resulted on significantly higher oxygen and water vapor permeabilities than those of the original bottle. Thermal analyses indicated increase in crystallinity values of post-consumer and reprocessed bottles, that led to a slowing down of the biodegradation process. © 2025 The Author(s)